2016
DOI: 10.1103/physrevb.94.115408
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the metal-insulator transition of donor-dopedSrTiO3

Abstract: The electrical properties of donor-doped SrTiO 3 (n-STO) are profoundly affected by an oxidation-induced metal-insulator transition (MIT). Here we employ dynamical numerical simulations to examine the hightemperature MIT of n-STO over a large range of time and length scales. The simulations are based on the Nernst-Planck equations, the continuity equations, and the Poisson equation, in combination with surface lattice disorder equilibria serving as time-dependent boundary conditions. The simulations reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 94 publications
(129 reference statements)
1
61
0
Order By: Relevance
“…11 In addition, Mikheev et al attributed the magnitude of the resistive switching properties of a Pt/Nb:SrTiO 3 junction to charges trapped in an unintentional contamination layer. 4 [14][15][16][17] A comparable scenario has been proposed also for electron gases formed at interfaces of SrTiO 3 . [18][19][20] Classical defect chemistry of donor-doped bulk SrTiO 3 is generally accepted for elevated temperatures above 1200 K. 21 At lower temperatures, however, it might not be possible to equilibrate either of the ionic sublattices in the entire sample due to sluggish ionic movement.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 64%
See 4 more Smart Citations
“…11 In addition, Mikheev et al attributed the magnitude of the resistive switching properties of a Pt/Nb:SrTiO 3 junction to charges trapped in an unintentional contamination layer. 4 [14][15][16][17] A comparable scenario has been proposed also for electron gases formed at interfaces of SrTiO 3 . [18][19][20] Classical defect chemistry of donor-doped bulk SrTiO 3 is generally accepted for elevated temperatures above 1200 K. 21 At lower temperatures, however, it might not be possible to equilibrate either of the ionic sublattices in the entire sample due to sluggish ionic movement.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 64%
“…2017) and the reported surface potential obtained from a defect chemical oxidation model at 1500 K. 15 Furthermore, Higuchi et al found the differences in the BE of 0.7 eV for 2 at. % donor-doped and 2 at.…”
Section: -5mentioning
confidence: 96%
See 3 more Smart Citations